(sinX+cosX)(tanX+cotX)=secX+cosecX prove both are equal
Answers
Answered by
2
↑Above is the required answer.
Note: I used A instead of X.
Note: I used A instead of X.
Attachments:
![](https://hi-static.z-dn.net/files/dca/9a0ca20e01300a5952c7dc910aedaeb7.jpg)
Answered by
1
Hi friend,
Here is your answer,
_____________________________________________________________
To prove : (sinx+cosx)(tanx+cotx) = secx+cosecx
LHS = (sinx+cosx)( sinx + cosx )
cosx sinx
= (sinx+cosx )(sin²x+cos²x)
(cosx.sinx)
= (sinx+cosx)( 1 )
(cosx.sinx)
= (sinx+cosx)
cosx.sinx
= sinx + cosx
cosx.sinx cosx.sinx
= ¹/cosx + ¹/sinx
= secx + cosecx
= RHS
Hence Proved.
_____________________________________________________________
★★★★ HOPE THIS HELPS YOU ★★★★
★★★★ PLS MARK ME AS BRAINLIEST ★★★★
Here is your answer,
_____________________________________________________________
To prove : (sinx+cosx)(tanx+cotx) = secx+cosecx
LHS = (sinx+cosx)( sinx + cosx )
cosx sinx
= (sinx+cosx )(sin²x+cos²x)
(cosx.sinx)
= (sinx+cosx)( 1 )
(cosx.sinx)
= (sinx+cosx)
cosx.sinx
= sinx + cosx
cosx.sinx cosx.sinx
= ¹/cosx + ¹/sinx
= secx + cosecx
= RHS
Hence Proved.
_____________________________________________________________
★★★★ HOPE THIS HELPS YOU ★★★★
★★★★ PLS MARK ME AS BRAINLIEST ★★★★
Similar questions